Dendriform pulmonary ossification: Report of two cases - Jamjoom, Lamia; Meziane, Moulay; Renapurkar, Rahul D (Indian Journal of Radiology and Imaging, 2013)
Dendriform pulmonary ossification is a rare form of diffuse pulmonary ossification that is usually detected incidentally on chest radiographs or chest computed tomography (CT) imaging. In this article, we present two patients who were incidentally found to have dendriform pulmonary ossification on chest imaging. The article will present the history and imaging findings of these two cases and then review the clinical, histological, and radiographic manifestations of dendriform pulmonary ossification.
Keywords: Dendriform pulmonary ossification; chest radiography; computed tomography